2007
DOI: 10.1590/s0004-282x2007000700003
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic right/left asymmetries in the neurons of the human hippocampal formation: a quantitative Golgi study

Abstract: -Objective: To search for right/left asymmetries in the dendritic trees of the neuronal populations and in the cell-free layer volumes of the human hipoccampal formation. Method: In necropsic material obtained from six male individuals we performed a quantitative Golgi study of the dendritic trees of dentate granules, CA3 and CA1 pyramidal neurons and a volumetric analysis of dentate gyrus molecular layer, strata oriens plus alveus and strata lacunosum-moleculare plus radiatum of CA3 and CA1 fields. Results: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We speculate that hippocampus on two sides show different sensitivity to radiation and chemotherapy toxicity due to subtle lateralized differences in cytoarchitecture. The hippocampal formation is more complex in the left side than the right, as it has been reported the total number of granule cells of dendritic segments is larger in the left than that in the right, suggesting that they have a larger receptor surface (17). Radiation or chemotherapy induces toxicity shows a decrease of dendritic branching and spine volume, which are more obvious in the left hippocampus than in its counterpart.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We speculate that hippocampus on two sides show different sensitivity to radiation and chemotherapy toxicity due to subtle lateralized differences in cytoarchitecture. The hippocampal formation is more complex in the left side than the right, as it has been reported the total number of granule cells of dendritic segments is larger in the left than that in the right, suggesting that they have a larger receptor surface (17). Radiation or chemotherapy induces toxicity shows a decrease of dendritic branching and spine volume, which are more obvious in the left hippocampus than in its counterpart.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, ours is the first study that reveals the findings of GM volume deficit in hippocampus of NPC patients who received IMRT and the imaging evidence confirming that the RT damage to hippocampus. As is known, left hippocampus plays a particular role in verbal memory (17). The RTOG 0933 study (18), a single arm phase II multi-institutional trial, was conducted to evaluate the efficiency of the hippocampus sparing in brain metastasis patients who underwent wholebrain radiotherapy (WBRT).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, no significant hippocampal volume change in low-dose areas was also reported in 15 low-dose radiated head and neck cancer patients four to ten years after RT [43]. Interestingly, Shi et al [40] found GM atrophy only in the left hippocampus, suggesting that the left side has a larger receptor surface as the granule cells show a larger amount of dendritic segments [58]. GM was also significantly lower in the right pulvinar and the right middle temporal gyrus.…”
Section: Determination Of Anatomical/morphological Changes In Normal-mentioning
confidence: 80%
“…The evolutionary selected system for space-time information processing, including the morphology and spatial orientation of PyrNs, is the fundamental feature underlying the function of CNS. Experimentally observed hemispheric asymmetry of synaptic morphology of PyrNs explains well-known functional laterality of human perceptual and cognitive functions [158][159][160]. The morphology of PyrNs concerning the function was the focus of long-term attention in neuroscience.…”
Section: Pyramidal Neuronsmentioning
confidence: 97%